2015
DOI: 10.1155/2015/391032
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fixation System for Acetabular Quadrilateral Plate Fracture: A Comparative Biomechanical Study

Abstract: This study aims to assess the biomechanical properties of a novel fixation system (named AFRIF) and to compare it with other five different fixation techniques for quadrilateral plate fractures. This in vitro biomechanical experiment has shown that the multidirectional titanium fixation (MTF) and pelvic brim long screws fixation (PBSF) provided the strongest fixation for quadrilateral plate fracture; the better biomechanical performance of the AFRIF compared with the T-shaped plate fixation (TPF), L-shaped pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The biomechanical research conducted by Zha etc. [29]also has shown that compared with the quadrilateral spring plates of T-shaped, L-shaped and H-shaped, the reconstruction plate combined with long screws had higher biomechanical stability for the treatment of quadrilateral plate fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical research conducted by Zha etc. [29]also has shown that compared with the quadrilateral spring plates of T-shaped, L-shaped and H-shaped, the reconstruction plate combined with long screws had higher biomechanical stability for the treatment of quadrilateral plate fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Synthes has introduced precontoured quadrilateral surface plate reinforced with pelvic brim plate with a slot for a lag screw for fixation of quadrilateral plate fractures. In a biomechanical study by Zha et al, 5 multidirectional titanium infrapectineal plates provides strongest fixation for such fractures, however it requires a steep learning curve and also is associated with increased bleeding rates due to injury to corona mortis while using Stoppa approach.…”
Section: Discussionmentioning
confidence: 99%
“…A biomechanical study performed by Zha etc. [27] As the first propensity-matched cohort study that describes the use of anatomical titanium plate and the reconstruction plate of DAPSQ for quadrilateral plate fractures. Our data indicate that the utility of anatomical titanium plate had the advantages of shorter operation time, less bleeding and transfusion.…”
Section: Different From the Above-mentioned Methods The Fixation Tecmentioning
confidence: 99%